The Relation Between Window-To-Floor Ratio and Lux Values of Natural Lighting in Residential Houses - Nyssa, Amelia Rizyan (Program Studi Arsitektur, Fakultas Teknik, Universitas Katolik Parahyangan, 2025)
Rapid population growth and increasing urban density have resulted in many residential houses experiencing inadequate natural lighting. One contributing factor to this condition is the disproportionate size of window openings relative to the interior floor area. This study aims to analyze the relationship between the Window-to-Floor Ratio (WFR) and natural daylight levels in residential buildings. The research employs an experimental approach consisting of two stages: (1) reviewing existing WFR standards in Southeast Asia and Indonesia, and (2) testing their applicability using Dialux lighting simulations to determine the WFR percentage capable of achieving optimal illuminance levels in accordance with the Indonesian National Standard (SNI) for residential lighting. The case study focuses on a two-storey residential house located in Banjarmasin. The results indicate a clear correlation between WFR percentage and indoor illuminance levels. The study identifies that the optimal WFR value meeting SNI requirements is a maximum of 23%. Nevertheless, the practical application of this ratio should be supported by additional considerations, particularly the orientation of window openings, to ensure more accurate and context-sensitive natural lighting performance.